2021
DOI: 10.1063/5.0052248
|View full text |Cite
|
Sign up to set email alerts
|

Birthing of a daughter vesicle in a model system for self-reproduction vesicles

Abstract: Sakuma and Imai [Phys. Rev. Lett. 107, 198101 (2011)] established a temperature-controlled cyclic process for a model system of self-reproducing vesicles without feeding. The vesicle generates a smaller inclusion vesicle called “daughter vesicle” inside the original vesicle (we call this “mother vesicle”) and then the daughter vesicle is expelled through a small pore on the mother vesicle. This self-reproducing process is called birthing. In the present study, we present a theoretical model on the birthing pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Previous research based on simulations by the Imai group 12 showed a similar phenomenon with DPPC/DPPE vesicles as ours and established a relationship between the ratio (Ratio r = r d / r p ) of the radius of the daughter vesicle ( r d ) and the parent vesicle ( r p ). In our study, we found a relationship between the success of the birthing process and the size of parent vesicles in all OA-containing vesicles.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Previous research based on simulations by the Imai group 12 showed a similar phenomenon with DPPC/DPPE vesicles as ours and established a relationship between the ratio (Ratio r = r d / r p ) of the radius of the daughter vesicle ( r d ) and the parent vesicle ( r p ). In our study, we found a relationship between the success of the birthing process and the size of parent vesicles in all OA-containing vesicles.…”
Section: Resultssupporting
confidence: 81%
“…(ii) In some cases, after morphological changes, budding or birth of vesicles are observed and are studied in terms of mechanical properties and free energy change. 12 However, these studies have not reported the membrane properties and composition of newborn vesicles because of the difficulty of analysis. (iii) Studies using a similar analysis method to the one presented here are often performed in the steady state (at a constant temperature) and are sometimes difficult to conduct in a time-lapse manner in a non-equilibrium state, such as heat flow, which imitates the environment of the cell and primordial protocells.…”
Section: Introductionmentioning
confidence: 99%
“…6(c) and (d)). 55,56 2.2.3 pH-induced changes in membrane curvatures. Changes in pH can affect the physicochemical properties of hydrophilic head groups of lipids (such as charges and solubility in water), which determine the hydrophile lipophilic balance (HLB) value of the lipids.…”
Section: Membrane-curvature-directed Divisionmentioning
confidence: 99%
“…Examples include thermally driven fission of protocells [243] and division by "birthing" of an internally assembled daughter vesicles due to membrane contraction and pore formation in the mother vesicle upon cooling. [244,245] The presence of the synthetic lipid DLPE appears to be necessary for the latter process. However, this does not strictly exclude that other lipid species or lipid mixtures would support similar pathways in nature.…”
Section: Divisionmentioning
confidence: 99%
“…[189,248] The "birthing" mechanism, where the size of the mother vesicle is not changing, is also a pseudo division phenomenon. [244,245] Besides these experimental works, there are computational division models. [249] Theoretical work on protocell growth and division will be discussed further in the section Protocells in silico.…”
Section: Divisionmentioning
confidence: 99%